The influence of singing with text and a neutral syllable on Portuguese children´s vocal performance, song recognition, and use of singing voice - Pereira, Ana Isabel Lemos do Carmo (2019)
Research on children’s singing development is extensive. Different ages, approaches, and variables have been considered. However, research on singing with a neutral syllable versus singing with text is scarce and findings are inconclusive. Furthermore, little is known about children’s song recognition, and how text and melody interact along the learning process. In addition, the ability to use all vocal registers has not been of regular concern when investigating singing accuracy. Yet, it has been considered a pre-requisite towards accurate singing. The purpose of this dissertation was to investigate the influence of singing with text and a neutral syllable on children’s vocal performance, song recognition, and use of singing voice. Three studies were conducted with children aged 4 to 9, attending a private school in Lisbon. In Study One, two songs were taught over two periods of instruction and assessment. Period One involved the teaching of a song with text (Song 1) and a song with a neutral syllable (Song 2), whereas in Period Two the same two songs were taught with text (text was added to Song 2). At the end of each Period, children (n = 135) were individually audio recorded singing both songs and interviewed for those songs’ recognition (stimuli included songs with the same melody but different text, the same text but different melody, different text and different melody). Results revealed that singing with text seems to favor younger children in both Periods, and that girls scored higher than boys. In song recognition, findings reveal that the ability to decenter focus toward melody and text increases with age. Song 2 (taught with a neutral syllable during Period One) seems to elicit a wider range of recognition strategies. No significant relationship was found between the scores on vocal performance and the most valued component of a song (melody or text). In Study Two, children (n = 137) were administered with the Singing Voice Development Measure (SVDM). The use of singing voice was assessed, the singing accuracy on the pitches belonging to the measure criterion patterns was determined, as well as the relationship between both variables. A significant, strong and positive relationship was found between both variables with text and a neutral syllable. To sing with text or a neutral syllable did not affect children’s use of singing voice, but pattern singing accuracy scores were higher when singing with a neutral syllable. Given the nature of Study’s One and Study’s Two data, a third study was framed. The additional analysis sought to investigate the role of the use of singing voice, grade level, and gender on songs’ tonal achievement. Findings reveal that the use of singing voice with a neutral syllable is a common predictor for both songs’ tonal achievement. Gender predicts Song’s 1 tonal scores (higher for girls), but not Song’s 2 tonal scores. Overall results indicate the importance of a music program that includes songs and patterns with text and a neutral syllable. Implications for music education and needs for future research are addressed at the end.